2016
DOI: 10.1016/j.advwatres.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Lattice Boltzmann flow simulations and estimating uncertainty in the permeability of complex porous media

Abstract: A common way to simulate fluid flow in porous media is to use Lattice Boltzmann (LB) methods. Permeability predictions from such flow simulations are controlled by parameters whose settings must be calibrated in order to produce realistic modelling results. Herein we focus on the simplest and most commonly used implementation of the LB method: the single-relaxation-time BGK model. A key parameter in the BGK model is the relaxation time τ which controls flow velocity and has a substantial influence on the perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…This analysis indicates that the same intrinsic permeability should be obtained with different choice of model parameters at the Navier-Stokes level. However, both τ and N grid can affect calculated value of permeability as previously reported (Ferréol and Rothman, 1995;Pan et al, 2006;Hosa et al, 2016;Prestininzi et al, 2016) and demonstrated in the above 2D case. As Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This analysis indicates that the same intrinsic permeability should be obtained with different choice of model parameters at the Navier-Stokes level. However, both τ and N grid can affect calculated value of permeability as previously reported (Ferréol and Rothman, 1995;Pan et al, 2006;Hosa et al, 2016;Prestininzi et al, 2016) and demonstrated in the above 2D case. As Fig.…”
Section: Resultsmentioning
confidence: 83%
“…intrinsic permeability (Ferréol and Rothman, 1995;Spaid and Phelan, 1997;Pan et al, 2006;Hosa et al, 2016;Prestininzi et al, 2016). The standard LBM is regarded as an alternative method to computational fluid dynamics (CFD), equivalent to solving the incompressible (or near incompressible) NavierStokes equation.…”
Section: Introductionmentioning
confidence: 99%
“…Pore structure plays an important role in the properties of porous media. However, due to the complexity of microstructure and irregularity of pore structure, it is always a challenging task to predict permeability [4][5][6][7][8]. The microstructures of oolitic graintone and dolograinstone can be found in previous study [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Using the measured rock porosity, it is possible to determine a threshold in the grayscale, to discriminate between pores and rock, and use this threshold to filter the attenuation values of the X-ray microtomography image to generate a binary (0 for rock site, 1 for pore site) representation of the rock and the pore space [25]. The binarization process defines all voxels with monochromatic value less than a threshold to be pore space or void, and the rest to be solid and consequently the segmented porosity monotonously decreases with the threshold value [26]. In a combination with the breakthrough in computational methods, we can make direct flow simulations through the pore space of real rock samples to calculate their permeabilities.…”
Section: Introductionmentioning
confidence: 99%